Blog business and the laws: effects of non-compliance - Mohamed, Duryana (IFRD & UUM, 2015)
At present blogs businesses are popular to many online users. Some bloggers or business owners embark on this business just for a short period of time in order to test the marketability of their products while others rely totally on this medium in marketing their products and services. Nevertheless, there are bloggers who used this internet medium or social media to commit unlawful acts such as internet scams. In Malaysia, there are laws, Rules and Regulations governing the online transactions or electronic commerce but until this date there is no specific provision on blog business. The issues are whether owners of blog business should comply with the above laws, rules and regulations, the consequences of failure to comply with those laws and the liability of blog business owners to consumers under the Consumer laws. This paper will discuss the above issues by looking at the application of existing laws on blog business and the effect of non-compliance of those laws, Rules and Regulations.